Evaluasi daya terima dan nilai gizi cookies berbahan tepung kacang merah dan buah naga untuk pencegahan stunting - Denny Indra Setiawan; Mutia Reski Amalia; Novian Swasono Hadi; Jein Eka Wirahmi Taidi (Jurnal SAGO Gizi dan Kesehatan, 2025)
nutritional value. Red beans and red dragon fruit are superior local foods in the Gorontalo area which have high nutritional value and are generally only used as a mixture in mixed ice.Objective: Analyze the level of liking and nutritional value of cookies substituted with red beans and dragon fruit. Method: This research used a laboratory experimental design with a completely randomized design and 3 replications. The cookie formulation is the ratio of red bean flour and dragon fruit, namely formula 1(0%:0%), formula 2 (25%:50%), formula 3(50%:100%) and formula 4(75%:150%) . The liking level test was carried out on 60 somewhat trained panelists. Analysis of the liking level test data used the Friedman difference test followed by testing with a confidence level of 95% or α=5%. The nutritional value analysis was carried out using the TKPI 2020 approach.Results: The liking level test showed that there were differences in color (p=0,013), aroma (p=0,001) and texture (p=0,001), but there were no differences in taste components (p=0,110). The best formula is formula 3 cookies because it has the highest average value on the three components of the liking level test.Conclusion: Cookie formulation with a ratio of red bean flour and red bean flour formula 3 (50%:100%) is the best formulation and meets the criteria for additional food as PMT for toddlers.